Relative contribution of genetic, individual, and self‐efficacy factors to smoking cessation in a Chinese rural population. (13th February 2017) - Wang, Qiang; Li, Suyun; Li, Huijie; Yang, Xiaorong; Jiang, Fan; Zhang, Nan; Han, Mingkui; Jia, Chongqi
Abstract : Background and Objectives: Nicotine dependence is influenced by genetic, individual, and psychological factors. We aimed to examine whether nicotinic acetylcholine receptor genes (CHRN) were associated with smoking cessation (SC) using genetic risk score and compare the relative contribution of genetic, individual and self‐efficacy factors to SC. Methods: Eight hundred and nineteen male smokers (mean age: 59.62) were recruited from 17 villages of three counties in Shandong province, China. Thirty‐two single nucleotide polymorphisms (SNPs) in seven CHRN genes were genotyped. Logistic regression was used to explore the relationship between genetic risk score and SC. Dominance analysis was performed to compare the relative contribution of genetic, individual, and self‐efficacy factors on SC. Results: CHRNA3 genetic risk score was associated with SC. Dominance analysis showed that individual factor was the most important predictor for SC, followed by genetic and self‐efficacy factors. Conclusions: CHRNA3 was associated with successful SC. Individual factor had more contribution than genetic factor to SC. Scientific Significance: Our findings provide support to the role of CHRN genes in the etiology of smoking cessation using genetic risk score. Individual factor should be particularly valued in smoking control intervention. (Am J Addict 2017;26:161–166)